Pengaruh Kualifikasi Pendidikan dan Konsep Diri terhadap Motivasi Mengajar dan Budaya Kerja Guru Pendidikan Agama Islam di MAN Se-Kota dan Kabupaten Mojokerto - Setiawan, Akhmad Pandu (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The increasing of teaching motivation and teacher work culture is influenced by many factors, both from one of them is self concept and from one of them is a teacher education qualification. This study aims to explain the results of field studies on (1) Qualifications of PAI teacher education in MAN Se-Kota and Kabupaten Mojokerto. (2) PAI teacher self concept. (3) teaching motivation. (4) Work culture. (5) The influence of educational qualifications on teaching motivation. (6) The influence of educational qualifications on work culture. (7) The influence of self-concept on teaching motivation. (8) Influence of self concept to work culture. (9) The influence of educational qualifications and self-concepts on teaching motivation. (10) Influence of educational qualification and self concept to work culture. This research is a type of correlational quantitative research because this study aims to determine the direction and magnitude of the influence between the variables studied. The subjects of the study were teachers of PAI MAN Se-Kota and Kabupaten Mojokerto as many as 35 respondents. Data collection using questionnaires, observation, interviews and documentation. The collected research data is then analyzed using descriptive analysis technique and inferential analysis. Hypothesis testing of research using simple regression analysis and multiple regression analysis. The results showed that: (1) Qualification of PAI teacher education in MAN in Kota and Kabupaten Mojokerto in high enough category. (2) The self concept of PAI teachers in positive and fairly high category. (3) The motivation to teach PAI teachers in the category is quite high. (4) The working culture of PAI teachers in the category is quite good. (5) There is no significant influence of educational qualification on teachers' teaching motivation PAI obtained Fhit <Ftabel = 0.070 <4.14. (6) There is no significant effect of educational qualification on teacher work culture of PAI obtained Fhit <Ftabel = 3,828 <4.14. (7) There is significant influence from self concept to motivation to teach teacher of PAI obtained Fhit> Ftabel - 10,468> 4,14. (8) There is significant influence from self concept to teacher work culture obtained Fhit> Ftabel - 26,359> 4,14. (9) There is a significant influence of educational qualification and self-concept on teacher's motivation to obtain Fhit> Ftabel - 5,457> 3,29. (10) There is a significant influence of educational qualification and self-concept on teacher work culture obtained Fhit> Ftabel - 5,457> 3,29. Self concept variable that is intrinsic factor of teacher give higher contribution.